The inhibitory role of melatonin on isolated guinea-pig urinary bladder: an endogenous hormone effect - Semerciöz, A; Onur, R; Ayar, A; Orhan, I (Wiley, 2004)
OBJECTIVE To investigate the effects of melatonin, an endogenous hormone, on acetylcholine and KCl-induced contractions of isolated guinea-pig detrusor muscle. MATERIALS AND METHODS Detrusor smooth muscle strips isolated from guinea-pig bladders were placed in an organ bath containing physiological saline at 37 degreesC and pH 7.4, constantly bubbled with 95% oxygen and 5% CO2. The effects of cumulatively applied melatonin on the acetylcholine- and KCl-induced contractions of isolated bladder strips were examined using isometric contraction measurements. RESULTS Melatonin (100 and 300 mumol/L) significantly inhibited the peak amplitude of both acetylcholine (10 mumol/L) and KCl (30 mmol/L)-induced contraction of the isolated bladder strips (P < 0.05). Similarly, melatonin caused a significant reduction in the contractile frequency induced by KCl (eight strips) in a concentration-dependent manner, while having no significant effect on the frequency of contractile response to acetylcholine, even at the highest concentration (300 mu mol/L) used (P = 0.58, 14 strips). CONCLUSIONS These results suggest that melatonin inhibits acetylcholine- and KCl-induced contractions in isolated bladder strips from guinea pigs. The endogenous nature of melatonin, with its low side-effect profile, makes it a potentially useful agent to be considered in the medical management of the overactive bladder.
Keywords: bladder; detrusor; contraction; melatonin; inhibition